2020
DOI: 10.3389/fmicb.2020.586148
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Activity and Community Composition Shape Bacterial Responses to Size-Fractionated Marine DOM

Abstract: To study the response of bacteria to different size-fractions of naturally occurring dissolved organic matter (DOM), a natural prokaryotic community from North Atlantic mesopelagic waters (1000 m depth) was isolated and grown in (i) 0.1-μm filtered seawater (CONTROL), (ii) the low-molecular-weight (<1 kDa) DOM fraction (L-DOM), and (iii) the recombination of high- (>1 kDa) and low-molecular-weight DOM fractions (H + L-DOM), to test the potential effect of ultrafiltration on breaking the DOM size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
(102 reference statements)
0
11
0
Order By: Relevance
“…6B ). These 3 families could be involved in the carbon, nitrogen, and phosphorus biogeochemical cycles by removing or transforming various substrates such as sugars, chitin, and organic acid ( 33 35 , 38 , 39 ) during the early stage of rearing. However, the Pearson correlation showed that only the Marinobacteraceae were a biomarker related to the “Nauplii Good” condition ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6B ). These 3 families could be involved in the carbon, nitrogen, and phosphorus biogeochemical cycles by removing or transforming various substrates such as sugars, chitin, and organic acid ( 33 35 , 38 , 39 ) during the early stage of rearing. However, the Pearson correlation showed that only the Marinobacteraceae were a biomarker related to the “Nauplii Good” condition ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we did not find a correlation between eCFs and ASV richness (SChao 1 ) or the Shannon diversity index. However, those indices may not reflect whether specific microbial taxa are relevant in the degradation of marine DOM 13 . Nevertheless, our study displayed shifts in eCF values which might be partially related to several specific groups.…”
Section: Discussionmentioning
confidence: 99%
“…Depth-dependent biogeographical patterns of CFs, and in turn PHP, are likely dependent on both the availability of substrates for prokaryotic activity as well as on the capability of certain microorganisms to use those resources depending on their nature and quality 13 . Therefore, the composition of the DOM pool may have a role in shaping bacterial community structure and vice versa 14 , 15 , and these factors likely influence PHP, as well.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these studies, the molecular size and chemical composition of DOC, which are likely linked to its variable radiocarbon age (via D 14 C), appeared to be the primary controls on its bioavailability and degradation in the ocean (Walker et al, 2011;Walker et al, 2016;Shen and Benner, 2020). In addition to quantifying the removal of oceanic DOC, these experiments were also used as platforms to assess the transformation of DOC composition as well as the concomitant shifts in microbial community structures (Carlson et al, 2004;Liu et al, 2020;Varela et al, 2020). While these bioassay experiments focused on the microbial degradation of DOC and provided potential linkages between DOC utilization and microbial lineages, the variation in the D 14 C-DOC values (or radiocarbon ages) during DOC degradation is still enigmatic and only supposed, lacking direct evidence of simultaneous carbon isotope measurements of DOC (both d 13 C-DOC and D 14 C-DOC).…”
Section: Introductionmentioning
confidence: 99%